Kesiapan UMKM Terhadap Implementasi SAK EMKM (Studi UMKM Di Kabupaten Blora) - Sholikin, Ahmad; Setiawan, Ade (JIFA (Journal of Islamic Finance and Accounting), 2018)
SMEs has an important role in economic development in Indonesia. In this development, SMEs has several obstacles. One of them is the preparation of financial statements that are not in accordance with accounting standards in Indonesia. SAK ETAP is a standard for SMEs in preparing financial statements. However, many studies have suggested that the majority of SMEs in Indonesia have not been able to implement SAK ETAP because the standard are too complex. Therefore DSAK IAI publishes new financial accounting standard for SMEs which is SAK EMKM effective on January 01, 2018. The new standard is intended to assist the needs in the preparation of financial statements. The result of this research shows the level the readiness of SMEs in implementing SAK EMKM. In conducting this research, the researcher used descriptive qualitative research. The researcher collects the data of this research from the interview and documentation. The analysis is dine by data reduction, data presentation, and conclusion. The results of this research shows that two SMEs in Blora Regency are not ready in applying SAK EMKM. The absence of SMEs have not done the preparation of financial statements.